2010
DOI: 10.1578/am.36.2.2010.129
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Steller Sea Lion (<I>Eumetopias jubatus</I>) Predation on a Harbor Seal (<I>Phoca vitulina richardii</I>) in the Glacier Bay Region of Southeastern Alaska

Abstract: Pinnipeds prey primarily on fish and invertebrates; however, several species are known to prey upon other pinniped species. Herein, we document an observation of a Steller sea lion (Eumetopias jubatus) attacking and partially consuming a juvenile harbor seal (Phoca vitulina richardii) in Johns Hopkins Inlet in Glacier Bay National Park, Alaska. Population trends for Steller sea lions and harbor seals contrast dramatically in the Glacier Bay region. Although other marine predators are known to attack harbor sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…, Visser et al . , Womble and Conlon ). It is also the most common behavior employed by leopard seals when processing large prey such as penguins or other seals (Erb , Edwards et al .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…, Visser et al . , Womble and Conlon ). It is also the most common behavior employed by leopard seals when processing large prey such as penguins or other seals (Erb , Edwards et al .…”
Section: Discussionmentioning
confidence: 95%
“…Both Australian fur seals and subantarctic fur seals used this as their main prey-processing method when consuming large fish (Hocking et al 2016). Shake feeding is also used by a number of other otariids when processing large prey like seabirds or other pinnipeds (Warneke and Shaughnessy 1985, Robinson et al 1999, Visser et al 2008, Womble and Conlon 2010. It is also the most common behavior employed by leopard seals when processing large prey such as penguins or other seals (Erb 1993, Edwards et al 2010.…”
Section: Discussionmentioning
confidence: 99%
“…However, as demonstrated by the fur seals in this study, many other species of pinniped are able to use very similar prey processing behaviors to leopard seals when handling prey that is too large to swallow whole. Warneke and Shaughnessy (1985) suggested that wild Australian fur seals are capable of processing fish of up to 1.5 m in length and octopus with tentacle length of up to 1 m. Antarctic fur seals have also been observed processing penguins by shaking and Steller sea lions (Eumetopias jubatus) use this method to process harbor seal pups into pieces small enough to swallow (Visser et al 2008, Womble andConlon 2010). Hence, it is inappropriate to separate out leopard seals as the only specialist "grip and tear" feeding species, especially since they display perhaps greater specialization towards filter feeding on krill (Hocking et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…), but cases of consumption of mammals are also known. Harbor seals ( Phoca vitulina ) are the most commonly reported mammals to be eaten by Steller sea lions (Pitcher , Pitcher and Fay , Calkins and Pitcher , Mathews and Adkison , Womble and Conlon ). Other pinnipeds consumed by Steller sea lions include ringed seals ( Pusa hispida ) (Tikhomirov , ), northern fur seals ( Callorhinus ursinus ) (Gentry and Johnson ), spotted seals ( Phoca larga ), bearded seals ( Erignathus barbatus ) (Calkins ), and California sea lions ( Zalophus californianus ) (Byrnes and Hood ), but no cases of cannibalism by Steller sea lion have been reported.…”
Section: Behavior Of the Infanticidal Male And Its Impact On Pup Mortmentioning
confidence: 99%